2005
DOI: 10.1097/01.gim.0000159898.90221.d3
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome carrier screening in the prenatal genetic counseling setting

Abstract: Purpose: To document our experience with fragile X carrier screening. Methods: In this study, 29,103 women with no known or suspected family history of fragile X syndrome were offered fragile X carrier screening during their prenatal genetic counseling visit. Screening acceptance was analyzed by referral indication, carrier frequencies documented, and prenatal outcome data presented. Results: Overall, 7.9% accepted carrier screening. The premutation frequency was 1 in 382, and the intermediate allele frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 23 publications
0
49
1
Order By: Relevance
“…The majority were with pregnant women (Berkenstadt et al 2007;Cronister et al 2005;Fanos et al 2006;Huang et al 2003;Pesso et al 2000;Spence et al 1996;Ryynanen et al 1999;Toledano-Alhadef et al 2001;Kallinen et al 2001), while some included relatively smaller numbers of nonpregnant women (Pesso et al 2000;Spence et al 1996;Toledano-Alhadef et al 2001;Berkenstadt et al 2007;Geva et al 2000). Most studies essentially focused on the uptake of testing, with rates varying between 7.9% ) and 21% (Spence et al 1996) in the USA, 80% in Israel (Pesso et al 2000), and 85% (Ryynanen et al 1999) and 92% respectively in two Finnish studies (Kallinen et al 2001).…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 99%
“…The majority were with pregnant women (Berkenstadt et al 2007;Cronister et al 2005;Fanos et al 2006;Huang et al 2003;Pesso et al 2000;Spence et al 1996;Ryynanen et al 1999;Toledano-Alhadef et al 2001;Kallinen et al 2001), while some included relatively smaller numbers of nonpregnant women (Pesso et al 2000;Spence et al 1996;Toledano-Alhadef et al 2001;Berkenstadt et al 2007;Geva et al 2000). Most studies essentially focused on the uptake of testing, with rates varying between 7.9% ) and 21% (Spence et al 1996) in the USA, 80% in Israel (Pesso et al 2000), and 85% (Ryynanen et al 1999) and 92% respectively in two Finnish studies (Kallinen et al 2001).…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 99%
“…2 Considering the severity of the syndrome, the frequency of the carrier status and the potential long-term benefits to the daughters knowing about their mother's screening result, the installment of population-based screening programs has been advocated repeatedly. [3][4][5] In addition, carrier status testing would also enable women into timely reproductive planning. 6 Even in the absence of a family history of the fragile X syndrome, the cost-effectiveness of prenatal genetic testing programs identifying the carrier status of women has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…42 In the largest US study to date (of over 119,000 tested), the overall carrier frequency among US females was 1.3% (0.61% for full mutation and 1.7% for premutation). 43 A recent large-scale study of 21,411 anonymous Canadian females (mothers of newborns) identified 1 in 549 as carriers.…”
Section: Fx 282: Premutationsmentioning
confidence: 99%